IMPROVING THE EFFICIENCY AND ADEQUACY OF URBAN ROAD-PASSENGER TRANSPORT - Pah, Jusuf J.S. (Jurnal Teknik Sipil, 2012)
This study offered ways to improve the efficiency and adequacy of urban public transport in Kupang, taking as the background the viewpoint that urban transport should concern not only middle and high income people but urban poor as well. It focused on three principle modes of public transport in the city, two of which are formal: city bus, and bemo, and the remaining one is informal/paratransit locally known as ‘ojek’. It took urban transport strategic review published recently by the World Bank as the quarry form which solutions for efficiency and adequacy the city’s passenger-transport were drawn and developed as to suit specific demand of the same. It concluded that to improve the service of public transport in the city, ‘competition-for the-market’ should be introduced into the market of its urban transport form of for-the-market competition recommended are route-concession. It stressed also however that prior to it state-owned motor companies should be privatized, and their capacity to engage in an open competition should be made better. As for bemo, service-contract should be introduced into the relation between the owner and the operators, whereas paratransit should be recognized and regarded as part of the whole urban public transportation system